Population structure and connectivity in the genus Molva in the North East Atlantic - Ilaria Coscia (Zenodo, 2023)
Genotype files in Structure format analysed in the paper " Population structure and connectivity in the genus Molva in the North East Atlantic", by Lydia McGill, Allan D. McDevitt, Bart Hellemans, Francis Neat, Halvor Knutsen, Stefano Mariani, Henrik Christiansen, Torild Johansen, Filip A. M. Volckaert , Ilaria Coscia .